ANALISIS KESALAHAN SISWA DALAM PEMAHAMAN KONSEP MENYELESAIKAN SOAL CERITA SPLDV DENGAN TAHAPAN NEWMAN - Shahnaz Juwita Az Zahra (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This research is a descriptive study that aims to find out the difficulties faced by students in solving the problem of understanding mathematical concepts. Indicators of the ability to understand concepts as learning outcomes of mathematics are as follows: (1) The ability to restate a concept; (2) The ability to clarify objects according to certain characteristics in accordance with the concept; (3) Ability to give examples and not examples; (4) Ability to present concepts in various forms of mathematical representation; (5) Ability to develop necessary requirements or sufficient requirements from a concept; (6) Ability to use, utilize and choose certain procedures; (7) Ability to clarify concepts or algorithms to problem solving. The subject of this study was 80 students of class VIII SMP PGRI 1 Cimahi 2017/2018 school year. The instruments in this study included the ability test sheet to understand concepts and interview guidelines. Based on the results of data analysis and discussion, it can be concluded that students cannot arrange the meaning of words that are thought in the form of mathematical sentences, less careful, forgetfulness, less practice in working on the problems of storytelling with varying ones and lack of understanding the questions.